Dental caries and periodontitis risk factors in cleft lip and palate patients - Wu, Qinrui; Li, Zhengyi; Zhang, Yixin; Peng, Xian; Zhou, Xuedong (Frontiers in Pediatrics, 2023)
Cleft lip and palate (CLP) is the most common congenital facial malformation and has a significant developmental, physical, and psychological impact on those with the deformity and their families. Risk factors contributing CLP may conclude as genetic factors and environmental factors. The anatomical and morphological abnormalities related to CLP are favorable for dental plaque accumulation on the tooth surface. Therefore, patients with CLP undergo poorer oral hygiene and higher susceptibility to dental caries and periodontitis. In this review, we aim to conclude and update probable causes underlying the association between CLP and poor oral health and provide novel ideas of targeted early prevention for such oral diseases.